Reye-like syndrome following treatment with the pantothenic acid antagonist, calcium hopantenate. - Noda, S (1988)
Three senile patients developed fatal acute encephalopathy while receiving calcium hopantenate. The clinical, biochemical, and pathological picture was similar to Reye's syndrome. Calcium hopantenate is a pantothenic acid antagonist. The serum levels of calcium hopantenate were high in coma, and that of pantothenic acid examined in one patient was lowered. Evidence obtained indicated that the Reye-like syndrome might be caused by calcium hopantenate possibly due to the induction of pantothenic acid deficiency.